1970
DOI: 10.1017/s0014479700000193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sowing Date, Nitrogen and Seed Rate on Wheat Yields in the Sudan Gezira

Abstract: A three-year study of the effects of sowing date, nitrogen application and seed rate on wheat showed that sowing in mid-October gave consistently greater grain yields than sowing in midSeptember or mid-November because grains were larger and more numerous per head. Nitrogen increased yields but the effect decreased with later sowing. Nitrogen probably increased grain yield by increasing the number of ears, but this effect diminished with higher levels of nitrogen. Grain yield was only slightly influenced by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…In the late 1960s, when wheat was introduced to the Gezira Scheme, the standard cultivars used were those already grown in the Northern Region of the Sudan which is characterized by longer and cooler winters. Mid-October was the optimum sowing date for those cultivars (Khalifa, 1970), but their grain yields were poor compared to those of the semi-dwarf cultivars introduced more recently. These newer varieties do not yield well from mid-October sowings and do best from November sowing dates.…”
Section: Discussionmentioning
confidence: 85%
“…In the late 1960s, when wheat was introduced to the Gezira Scheme, the standard cultivars used were those already grown in the Northern Region of the Sudan which is characterized by longer and cooler winters. Mid-October was the optimum sowing date for those cultivars (Khalifa, 1970), but their grain yields were poor compared to those of the semi-dwarf cultivars introduced more recently. These newer varieties do not yield well from mid-October sowings and do best from November sowing dates.…”
Section: Discussionmentioning
confidence: 85%
“…The recommended seed rate for all varieties of wheat in the different areas of production in the Sudan is 120 kg/ha. Khalifa (1970) and Dafalla & Khalifa (1974) reported that seed rates of 60, 120 and 180 kg/ha gave similar yields with Giza varieties; increases in yield were obtained only when seed rates increased from low levels up to 60 kg/ha. It was considered safer, however, to recommend a seed rate of 120 kg/ha for commercial production where hazards and lower standards of husbandry were expected.…”
Section: Discussionmentioning
confidence: 94%
“…vr .«-,/> o-i 7 ,r.*\ T>-• i. o -n. • from Egypt) and Mexipak (of Mexican origin). The Khalifa, 1970;Singh et al 1971;Kirby & Fans, . 6 J ± \ ' ,* , \ , .…”
Section: Introductionmentioning
confidence: 99%
“…The agronomic studies made in these countries and in the Sudan (Khalifa, 1970) have emphasized the limitation imposed by the short growing season on wheat grain yields. However, the influence of environmental conditions resulting from different sowing dates on the growth of wheat in such environments has been only partly investigated.…”
Section: Introductionmentioning
confidence: 99%